Evidence on the variation of idiosyncratic risk in house price appreciation - Jaqueson K. Galimberti; Lydia Cheung; Philip Vermeulen (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2022)
Using around one million repeat sales observations of single-family homes across New Zealand, over the period 1992 to 2021, we provide evidence that idiosyncratic risk in real house price appreciation varies considerably across houses. We find that idiosyncratic risk is time varying, depends negatively on the initial house price, varies strongly across locations and reduces significantly as the holding period of the house increases. Location is the most important of these factors. By buying an above the median house in a low-risk region, and holding on to the property for a longer period, households can significantly reduce idiosyncratic risk.
Keywords: G1; R1; 330; idiosyncratic risk; house prices; housing markets